2020
DOI: 10.3390/insects11070445
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cover Crop Termination on Ground Dwelling Arthropods in Organic Vegetable Systems

Abstract: A key aspect in cover crop management is termination before the cash crop is planted. The aim of this study was to assess the effects of termination methods on ground-dwelling arthropods. The conventional mechanical termination method—i.e., green manuring by means of a disc harrow—was compared to flattening using a roller crimper. Two different crop systems were investigated for two growing seasons; cauliflower was grown in autumn after the termination of a mixture of cowpea, pearl millet, and radish, and toma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Moreover, the ADs of ground and rove beetles were higher under NT‐RC plots, which are generally sensitive to soil disturbance (Pretorius et al, 2018; Rivers et al, 2017; Tamburini et al, 2016). Our results agree with previous studies regarding the effects of ASC termination on soil functional diversity (Depalo et al, 2020; Magagnoli et al, 2018). The NT‐RC strategy has been shown to reduce the direct impact of tillage (for ASC incorporation and weeding operations) on organisms living in the upper soil layers (Roger‐Estrade et al, 2010; Sommaggio et al, 2018) and to create favourable conditions (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the ADs of ground and rove beetles were higher under NT‐RC plots, which are generally sensitive to soil disturbance (Pretorius et al, 2018; Rivers et al, 2017; Tamburini et al, 2016). Our results agree with previous studies regarding the effects of ASC termination on soil functional diversity (Depalo et al, 2020; Magagnoli et al, 2018). The NT‐RC strategy has been shown to reduce the direct impact of tillage (for ASC incorporation and weeding operations) on organisms living in the upper soil layers (Roger‐Estrade et al, 2010; Sommaggio et al, 2018) and to create favourable conditions (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, both positive and negative effects have been observed on cash crop yields when NT‐RC is implemented under Mediterranean conditions (Canali et al, 2013; Ciaccia et al, 2016; Diacono et al, 2017). In addition, few studies have examined the impact of cover crop termination on beneficial soil fauna (Depalo et al, 2020; Magagnoli et al, 2018), root growth and soil nitrogen (Hefner, Canali, et al, 2020; Hefner, Gebremikael, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Rivers et al [56] also found an increase in ground beetle activity density and richness during their 3-year transition to organic experiment. However, previous studies were done either only for a short and transition to organic period [29,54,57] or in the established organic phase [30,58], which may not be representative of the temporal changes occurring during both transition to and established organic phases.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also disclosed fewer spiders in conventional than no-tillage systems [ 51 , 52 ]. However, a study investigating two cover crop termination practices (roller crimper vs. green manuring with a disk harrow) on ground predators showed that green manuring increased spider abundance [ 53 ]. The authors proposed that spiders responded to the enhanced detrital food chain that occurred after cover crop residue was incorporated into the soil.…”
Section: Discussionmentioning
confidence: 99%